Strategy for Optimizing Effa Design's Tiktok Content to Increase Engagement Rate - Syarifah Fadhilah; Siti Nurjanah (Universitas Pelita Harapan, 2024)
In the digital era, TikTok has become a vital tool for business promotion with over 1 billion active users. The